Understanding External Peak Demands in Elite vs. Non-Elite Male Basketball Players - Yoel Antoranz; Enrique Alonso-Pérez-Chao; Carlos Mª Tejero-González; Hugo Salazar; Juan del Campo-Vecino; Sergio L. Jiménez-Sáiz (Sports)
Background: Understanding the physical demands of basketball at different competitive levels is essential for optimizing training and performance. While elite players are often assumed to experience the highest physical loads, evidence comparing peak external demands (PDs) between elite and non-elite athletes using time-window analysis is limited. Therefore, the aim of this study was to examine how player level (Elite vs. Non-Elite) influences the external PDs experienced by male basketball players. Methods: This study examined PlayerLoad™ (PL) PDs in elite (n = 10) and non-elite (n = 11) male basketball players during the 2023–2024 season. Players were monitored using inertial measurement units (IMUs) during official and friendly matches (elite = 8 games; non-elite = 29 games). Peak PL values were computed using rolling averages across 30-s, 1-min, and 3-min time windows. Linear mixed-effects models were employed to examine differences between groups, adjusting for age and match nature. A secondary analysis was carried out including only friendly matches. Results: Non-elite players exhibited significantly higher PL PDs across all the time windows (p < 0.001), with effect sizes ranging from small to very large in the main analysis (ES = −0.41 to −2.11) and from very large to extremely large in the secondary analysis (ES = −2.68 to −5.06). Differences were more pronounced in longer durations. These results suggest that non-elite athletes sustain higher physical loads, possibly due to less efficient movement patterns and lower tactical regulation. Conclusions: Elite players display lower peak external loads than their non-elite counterparts, likely due to superior cognitive, tactical, and perceptual abilities that enhance movement economy. Training programs should incorporate tasks that combine physical intensity with decision-making demands to foster efficiency and potentially reduce injury risk.